Pemaknaan nilai kebangsaan dalam pembelajaran pendidikan agama Islam - Zikraini Syafitri, Ruhul; Tazkia, Khairunnisa; Neni, Neni (Jurnal Pendidikan Agama Islam, 2025)
This study explores the meaning of national values in Islamic Religious Education (PAI) learning. The research aims to analyze how students understand and internalize values such as patriotism, unity, tolerance, and social responsibility through PAI lessons. Data were collected through observations, interviews, and questionnaires involving teachers and students. The results indicate that integrating national values into PAI learning enhances students’ character development, promotes civic awareness, and strengthens moral values. However, challenges such as limited teaching resources and varying student engagement were identified. The study suggests that effective teaching strategies, supported by appropriate media and active learning methods, are essential to maximize the impact of PAI in fostering national values among students.